Melancholia [videorecording (DVD)] - Trier, Lars von, 1956-; Dunst, Kirsten, 1982-; Skarsgård, Alexander; Sutherland, Kiefer, 1966-; Hurt, John, 1940-2017; Gainsbourg, Charlotte, 1971- (Magnolia Home Entertainment, 2012)
In this beautifully filmed movie about the end of the world, Justine and Michael are celebrating their marriage at a sumptuous party in the home of her sister Claire , and brother-in-law John. A planet called Melancholia is heading directly towards Earth and threatening to collide. Meanwhile, tensions are mounting and relationships are fraying as the family deals with their fears.